Beyond digital repression: techno-authoritarianism in radical right governments - Alcides Eduardo dos Reis Peron; David Almstadter Mattar de Magalhães; Gabriel Fernandes Caetano (Cogent Social Sciences, 2025)
Over the past few years, governments have been using AI-based surveillance systems a crescent amount worldwide. Disguised as ‘smart’ methods for crime control, they have spread among democracies under the rule of radical right governments. Their employment, aligned with institutional and democratic disruptions, establishes forms of repression against those who challenge these governments. This study aims to discuss and broaden the emerging concept of techno-authoritarianism by highlighting the growing application of AI-based systems to underpin spying, surveillance practices, and state hacking in democracies, under radical right governments. It focuses on the uses of these tools by radical right governments in Israel, Brazil, and Hungary, demonstrating how they flourish in authoritarian contexts while creating conditions for new repressive practices. The perspective of techno-authoritarianism provides an accurate framework for understanding the role of the radical right in the spread and normalization of these systems on a global scale. It will initially explore the relationship between the rise of the international radical right, political tensions, and the proliferation of invasive technologies. Secondly, from the theoretical perspective of the Social Construction of Technology, it explores the connections between authoritarianism and technology, presenting the idea of techno-authoritarianism. Finally, it will briefly examine techno-authoritarian practices that have taken place in Brazil, Israel, and Hungary in recent years.